Associations Between Occupational Physical Activity, Low Back Pain and Disability Among Operating Room Personnel - Marzieh Mohammadi; Zeinab Kazemi; Marzieh Izadi Laybidi; Mohammad Sadegh Ghasemi (بهداشت و ایمنی کار)
Introduction: Operating room personnel are involved with occupational physical activities such as repetitive bending, holding surgical tools and standing for long hours that can lead to musculoskeletal disorders (MSDs). Low back pain (LBP) is the most prevalent and costly problem among these disorders. The aim of this study was to determine the relationship between occupational physical activity, LBP and disability among operating room personnel. Material and Methods: A total of 60 operating room personnel voluntarily participated in the study, all of which had at least two years of working experience. At the end of a working week, the degree of disability and pain were assessed by Graded Chronic Pain (GCP) questionnaire. The International Physical Activity Questionnaire (IPAQ) was used to evaluate the level of physical activity. Simple linear regression was conducted to investigate the relationship between physical activity, LBP and disability. Results: The survey using the GCP questionnaire revealed that 58.3% of participants reported experiencing occupational back pain, while 41.7% reported no back pain.  Among those with back pain, the average pain intensity was rated 43.11 (18.22) on the scale.  Pain remained stable for an average of 2.3 days (standard deviation = 0.95).  The average level of disability associated with back pain was 32.09 (27.44). Statistical analysis using simple linear regression showed a significant relationship between back pain and several factors: vigorous physical activity (p-value = 0.02), prolonged sitting time (p-value = 0.01), and chronic pain (p-value < 0.001). Conclusion: Occupational physical activity characterized by low intensity, but high repetition and standing for a long time in fixed postures were the most significant contributors to lumbar back pain among operating room personnel. Chronic pain in this population was reported as grade 2, indicating severe pain with minimal disability; if left unaddressed, this could lead to movement restrictions.